Male and Female Compliment Patterns and Topics Used by Bts Fans’ Comments on Hybe Labels: Pola dan Topik Pujian Pria dan Wanita yang Digunakan oleh Komentar Fans Bts di Hybe Labels - Risalatul Khabibah; Elisa Nurul Laili (Teaching English as Foreign Language, Literature and Linguistics, 2022)
Compliment is a polite expression of praise and admiration, an action or situation that implies admiration or respect. One of the important features that evaluation produces is compliments: compliments reflect cultural values, beliefs and speaker. Non-linguistic factor that can affect the use of language, such as compliments, is gender. Male and female use different words, so the manner they provide compliments are also different. This study was conducted to discover the male and female compliment patterns and topics used in BTS fans’ comments on the Hybe Labels’ YouTube channel. The researcher used qualitative descriptive method in this study. It analyzes the form of compliment given by male and female fans to BTS through YouTube comments. This final project explained, analyzed and interpreted the fan compliments to BTS. The results of this study showed that male and female BTS fans’ compliments follow a simple syntax pattern, using adjectival compliments rather than verbs of liking. These compliment topics are appearance, hard work, performance, possession, achievement, skill, and talent. The most used theme in this survey is compliment for skill, primarily from male fans. In summary, there is not much difference between male and female fans when it comes to complementing BTS's Dynamite music video on Hybe Labels' YouTube channel.